2005
DOI: 10.1210/jc.2004-0849
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Activators of Peroxisome Proliferator-Activated Receptors Are Reduced in Preeclamptic Pregnancy

Abstract: We previously described activators of peroxisome proliferator-activated receptor gamma (PPAR gamma) in the serum of pregnant women. We have also characterized this activating component by using a hexane-extracted serum fraction to examine PPAR activator levels in normal and preeclamptic (PE) pregnancies. In this study we report that the pregnancy PPAR activator is present in similar concentrations in serum and plasma. We also found that the activating fractions from pregnancy sera stimulate not only PPAR gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 32 publications
3
62
0
1
Order By: Relevance
“…In spontaneously hypertensive rats, there is reduced protein expression of placental PPAR-g (Mattace Raso et al, 2008). Waite et al (2005) demonstrated that serum extracts from pregnant women contained PPAR-g activators, and women with severe early-onset pre-clampsia had significantly reduced circulating PPAR-g activators compared with serum extracts from healthy pregnant women, suggesting that reduced PPAR-g activity may contribute to pre-clampsia . In contrast, Holdsworth-Carson et al (2010) examined placental expression of PPAR-g and demonstrated that placentas from women with pre-clampsia did not demonstrate any differences in mRNA or protein expression of PPAR-g compared with healthy controls (HoldsworthCarson et al, 2010).…”
Section: Pre-eclampsiamentioning
confidence: 97%
“…In spontaneously hypertensive rats, there is reduced protein expression of placental PPAR-g (Mattace Raso et al, 2008). Waite et al (2005) demonstrated that serum extracts from pregnant women contained PPAR-g activators, and women with severe early-onset pre-clampsia had significantly reduced circulating PPAR-g activators compared with serum extracts from healthy pregnant women, suggesting that reduced PPAR-g activity may contribute to pre-clampsia . In contrast, Holdsworth-Carson et al (2010) examined placental expression of PPAR-g and demonstrated that placentas from women with pre-clampsia did not demonstrate any differences in mRNA or protein expression of PPAR-g compared with healthy controls (HoldsworthCarson et al, 2010).…”
Section: Pre-eclampsiamentioning
confidence: 97%
“…10 In addition, recent data have demonstrated that serum concentrations of endogenous agonists of PPAR-␥ are significantly reduced in women with severe early onset preeclampsia compared with healthy pregnant women. 11 In contrast, Holdsworth-Carson et al 12 demonstrated that placentas from women with preeclampsia did not exhibit any changes in either PPAR-␥ activity or placental expression of PPAR-␥ mRNA and PPAR-␥ protein, thus whether aberrant PPAR-␥ activity is involved in the development of pregnancies complicated by hypertension is not known. Furthermore, because of the limitations of conducting studies in pregnant women, and the embryonic lethality of homozygous PPAR-␥ receptor gene knockout in rodents, 9 the functional role of PPAR-␥ in normal pregnancy remains unclear.…”
mentioning
confidence: 97%
“…4 PPAR-␥ plays a predominant role in normal vascular function 5 and in the differentiation of labyrinthine trophoblast lineages, 6 which, along with the fetal endothelium, form the vascular exchange interface with maternal blood. 7 A reduction in the placental expression of PPAR-␥ activators has been demonstrated in some women who develop severe preeclampsia, 8 and significantly higher PPAR-␥ DNA binding activity has been demonstrated in placentas from women with both intrauterine growth restriction and preeclampsia. 9 To investigate the role of PPAR-␥ as a potential therapeutic target for preeclampsia, we administered the PPAR-␥ agonist, rosiglitazone, to rats that had undergone reduced uterine perfusion pressure (RUPP) surgery.…”
mentioning
confidence: 99%